Peningkatan Belajar Mandiri Siswa Di Sekolah Melalui Layanan Informasi Dengan Media Sinematografi - Febriansyah Febriansyah (Institut Agama Islam Negeri (IAIN) Curup, 2020)
The research objective was to reveal whether there were differences in students' independent learning before (pre-test) and after (post-test) providing information services with cinematographic media. It was found that the phenomenon of student independent learning was low, the desire of students was less to learn, and the lack of understanding of students in learning. One type of guidance and counseling service that can be used to improve students' independent learning in schools is information services using cinematographic media. This research is a quantitative research with a Quasi Experiment model with One Group Pretest-Posttest Design. The population was students with a total of 99 students and a sample of 32 people who were determined purposively. How to collect data through self-learning scale. Data were analyzed using Paired Sampels T-Test with the help of SPSS version 20.00. The findings of the study show that information services using cinematographic media are effective for improving students 'independent learning in schools and there are differences in students' independent learning in schools in the pre-test and post-test after treatment using information services with cinematographic media. This research can be concluded that the independent learning of students in schools can be improved through information services with cinematographic media. This study shows that the importance of implementing information services with cinematographic media in schools by school counselors so as to improve students' independent learning in schools.